Changes of gene expression in peripheral blood mononuclear cells of lung cancer patients with or without anorexia. Issue 1 (January 2023) - Molfino, Alessio; Ambrosani, Francesca; Tambaro, Federica; Belli, Roberta; Imbimbo, Giovanni; Udali, Silvia; Moruzzi, Sara; Pattini, Patrizia; Ramaccini, Cesarina; Castagna, Annalisa; Muscaritoli, Maurizio; Friso, Simonetta
Summary: Background & aims: Anorexia is a disabling symptom in cancer and we aimed at investigating the role of changes in gene expression in lung cancer patients presenting with anorexia. Methods: Genome-wide transcriptomic profiling was assessed in PBMCs RNA from newly diagnosed lung cancer patients and in a control group. RT-qPCR was used for selected genes. Results: RNA-Seq analysis revealed among groups a large number of differentially expressed genes mainly implicated in immune system regulation, oxidative stress and cytokine-mediated inflammation signaling pathways. In particular, we identified a total of 983 DEGs (843 up-regulated; 140 down-regulated) in anorexic cancer compared to controls. A selected number of DEGs including ADAM8, SMAD4, CCR4 and CLU were differentially expressed within cancer group according to the presence/absence of anorexia. In terms of RT-qPCR, ADAM8 was less expressed in cancer patients than controls (p < 0.001), and in anorexic patients vs controls (p = 0.001). The expression of SMAD4 was lower in cancer vs controls (p = 0.005), and in anorexic patients vs controls (p = 0.009). We observed lower CCR4 expression in both anorexic and non-anorexic vs control (p = 0.004, p = 0.011, respectively) and a similar trend was present for CLU . Conclusions: Our data shed new light on the role of specific genes and their associated molecular pathways as potential key mechanisms for the development of anorexia and may represent a novel landmark for understanding the complex pathophysiology of impaired appetite in cancer.